Technology and its Importance in Teaching Foreign Language Skills - Ravshanova Nasiba Karamatovna (Zien Journals, 2022)
This article deals with the issue of the integration of technology into language teaching and its role in improving writing and reading skills in foreign language classes. There were introduced the importance of technological tools and some practical implementations in using them for enhancing learners’ writing and reading skill. The ideas were proved by the facts that student’s skills can be significantly increased by various technological tools such as wikis, quick pen, questionary as well as blogging. Practicality of using blogs is proved by given activities and lesson plans as well. These tools help to form and develop students` communicative competences, linguistic, pragmatic, socio-linguistic and strategic as well as their writing and reading skills.
Keywords: Technology; Computer assisted language learning; communicative language teaching; practical application